Padrões e processos de diversificação de pequenos mamíferos não voadores na Amazônia oriental - Silva, Victor Fonsêca da (2018)
Phylogeography studies of non-flying small mammals in the Amazon initiated in the 1990s and since then, although several publications have addressed this theme, this type of work is still insipient, especially for the region of eastern Amazon. In order to carry out a study about the diversification of non-flying small mammals, we used four species, Marmosa murina, Hylaeamys megacephalus, Oecomys paricola and Marmosops pinheiroi, with distribution in the eastern Amazon. Analyzes were based on mitochondrial (cytochrome b and mitochondrial DNA control region) and nuclear markers (Intron 7 Beta Fibrinogen and Retinoid Interphotoreceptor Binding Protein), as well as new generation sequencing data (RADseq) for Oecomys paricola species. We found that Marmosa murina and Hylaeamys megacephalus present four lineages that have diversified in the Pleistocene. In relation to Marmosops pinheiroi, we identified six lineages that began their diversification in the Pliocene with the separation of two large clades on the opposite banks of the Xingu river, and the emergence of each lineage only in the Pleistocene. For Oecomys paricola, our analysis based on mitochondrial markers showed the existence of four lineages, while RADseq data indicated the existence of three lineages with the separation occurring exclusively in the Pleistocene. We have documented here the importance of the Amazonas, Tapajós, Xingu and Tocantins rivers for the diversification of this group of non-flying small mammals, with the history recovered by molecular markers leading us to the conclusion that this diversification is complex and the product of several processes. Finally, based on the 17 lineages identified we suggest that nine of them are corresponding for revalidation or description.